2019
DOI: 10.24251/hicss.2019.700
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality on Code Reuse

Abstract: The ubiquity and necessity of computer software requires programmers to reuse extant code to keep up with increasing software demands. Researchers have started to investigate the underlying psychological processes and the programmer characteristics affecting code reuse. The present study investigated the role of programmer personality (propensity to trust, suspicion propensity) on willingness to reuse code. Programmers were recruited through Amazon's Mechanical Turk. Programmers completed propensity to trust a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They found that propensity to trust was a significant predictor of betting behaviors when participants bet a small wager amount, but not medium or large wagers. Other research showed that trait trust was predictive of behaviors in the Investment Game (Evans & Revelle, 2008) and that trait suspicion was predictive of software reuse (Ryan et al, 2019). As people high in suspicion propensity suspend their judgment, they may also continue to process information in the betting context leading to betting behaviors only when they have reached a threshold of certainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that propensity to trust was a significant predictor of betting behaviors when participants bet a small wager amount, but not medium or large wagers. Other research showed that trait trust was predictive of behaviors in the Investment Game (Evans & Revelle, 2008) and that trait suspicion was predictive of software reuse (Ryan et al, 2019). As people high in suspicion propensity suspend their judgment, they may also continue to process information in the betting context leading to betting behaviors only when they have reached a threshold of certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Other research considered the influence of suspicion propensity on behaviors. Ryan and colleagues (2019) demonstrated suspicion propensity predicted software reuse. Computer programmers were asked whether they would reuse code that had been manipulated in terms of readability, organization, and reputation.…”
Section: Propensity To Trustmentioning
confidence: 99%
“…Indeed, in the interpersonal trust literature, the antecedents to trust a referent vary depending on the amount of time and experience a trustor has with a referent [5,25]. In addition, research on trust in code has found that user personality has an impact on perceptions of and trust in computer code [20,26]. Future research would benefit from investigating the interplay of user characteristics and code manipulations on trust in code before and after testing the claims of metadata.…”
Section: Limitations and Future Workmentioning
confidence: 99%